Self-Deception in Terminal Patients: Belief System at Stake - Echarte, Luis E.; Bernacer, Javier; Larrivee, Denis; Oron, J. V.; Grijalba-Uche, Miguel (Frontiers in Psychology, 2016)
A substantial minority of patients with terminal illness hold unrealistically hopeful beliefs about the severity of their disease or the nature of its treatment, considering therapy as curative rather than palliative. We propose that this attitude may be understood as self-deception, following the current psychological theories about this topic. In this article we suggest that the reason these patients deceive themselves is to preserve their belief systems. According to some philosophical accounts, the human belief system (HBS) is constituted as a web with a few stable central nodes – deep-seated beliefs – intimately related with the self. We hypothesize that the mind may possess defensive mechanisms, mostly non-conscious, that reject certain sensory inputs (e.g., a fatal diagnosis) that may undermine deep-seated beliefs. This interpretation is in line with the theory of cognitive dissonance. Following this reasoning, we also propose that HBS-related self-deception would entail a lower cognitive load than that associated with confronting the truth: whereas the latter would engage a myriad of high cognitive functions to re-configure crucial aspects of the self, including the setting of plans, goals, or even a behavioral output, the former would be mostly non-conscious. Overall, we believe that our research supports the hypothesis that in cases of terminal illness, (self-)deceiving requires less effort than accepting the truth.